An update on the latest chemical therapies for reflux esophagitis in children. (22nd January 2019) - Bardou, Marc; Fortinsky, Kyle J.; Chapelle, Nicolas; Luu, Maxime; Barkun, Alan
ABSTRACT: Introduction : Gastroesophageal reflux (GER), and its complicated form gastroesophageal reflux disease (GERD) is a common condition in infants and children. As GERD is often considered to cause extra-oesophageal symptoms in children and in the absence of standardized diagnostic and treatment algorithm, many children are inappropriately exposed to empirical anti-reflux treatments, with Acid-Suppressive Medications (ASM); mostly proton pump inhibitors (PPIs). Areas covered : The authors summarize the pharmacological management of pediatric GERD and discuss the efficacy of PPIs as randomized controlled trials have failed to demonstrate their clinical efficacy in the pediatric population. They consider the controversies surrounding the use of PPIs in the pediatric population as increasing evidence suggests of, although controversially, an increased risk of adverse events such as infection of the respiratory or gastrointestinal tract. Esophagitis is a complication that has a significant impact on weight gain and growth, as well as on the quality of life, and in such case, the benefit of treatment largely outweighs the risk. Expert opinion : Clinicians should reserve ASM use for infants and children with proven esophagitis and avoid their routine use in patients with merely symptoms of GER. Treatment need and options must be frequently re-evaluated to reduce the risks associated with ongoing therapy.